Shaking Table Experiment and Energy Analysis of a New Rebar Isolation Pier - Yifu Xiao; Shouping Shang; Zhen Wang (Advances in Civil Engineering)
This paper introduces the structure and principle of a new isolation device—rebar isolation pier—which is mainly composed of vertical steel bar and asphalt ointment. It is used to reduce the earthquake action of the building structure. Compared with other isolation devices, the rebar isolation pier has the following advantages: simple structure, convenient construction, low cost, simple maintenance, and easy to fetch material. In the experiment, the test model is a two-layer frame, and the Taft wave and the Wolong wave were selected to simulate the actual earthquake. In order to study the damping effect of asphalt ointment, two different isolation piers (filled and unfilled with asphalt ointment) were included. The dynamic characteristics and isolation effect of the rebar isolation pier are studied by analysis of acceleration, displacement, and hysteresis loops. At the same time, according to the principle of energy method, the energy balance equation of the rebar isolation pier was proposed, and the total input energy and damping energy are used to analyze the energy of the isolation pier. The results demonstrate that the rebar isolation pier can effectively reduce the natural frequency, acceleration response, and absorbed seismic energy of the structure when the peak ground acceleration reaches 0.3 g, and it still has the potential to withstand greater seismic action.